On repdigits powers in base beta - Belovas, Igoris (Lietuvos matematikos rinkinys, 2022)
The article presents formulas for powers of repdigits in the different numeral systems. This task can be used as an exercise for computer science students to help them master the corresponding mathematical apparatus.
Keywords: repdigits; numeral systems